Correction: Structure and function relationships in alkylammonium lead(ii) iodide solar cells. Issue 17 (7th May 2015) - Safdari, Majid; Fischer, Andreas; Xu, Bo; Kloo, Lars; Gardner, James M.
<x xml:space="preserve">Abstract</x> Correction for 'Structure and function relationships in alkylammonium lead(ii) iodide solar cells' by Majid Safdari et al., J. Mater. Chem. A, 2015, DOI: 10.1039/c4ta06174h.